1995
DOI: 10.1111/j.1748-8583.1995.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Collectivism and the Management of Industrial Relations In Greenfield Sites

Abstract: Patrick Gunnigle examines management approaches to industrial relations in newly established (‘greenfield’) companies in the Republic of Ireland. He focuses particularly on recent empirical findings on trade union density and recognition and on the role of employer organisations. the evidence presented points to newly emergent patterns of industrial relations management which diverge from the pluralist model. However, in only a minority of cases could these be classified as ‘soft’ human resource management. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 14 publications
3
73
1
2
Order By: Relevance
“…This is illustrative of broader trends in the US MNC sector more generally. In this regard our cases confirm the growing incidence of the establishment of US subsidiaries in Ireland on a non-union basis (see also, Gunnigle, 1995;Roche, 2001) Act. Nonetheless the union movement have continued to press their agenda with regard to statutory recognition legislation and are likely to continue to do so in the context of declining union recognition.…”
Section: Voluntarismsupporting
confidence: 71%
See 2 more Smart Citations
“…This is illustrative of broader trends in the US MNC sector more generally. In this regard our cases confirm the growing incidence of the establishment of US subsidiaries in Ireland on a non-union basis (see also, Gunnigle, 1995;Roche, 2001) Act. Nonetheless the union movement have continued to press their agenda with regard to statutory recognition legislation and are likely to continue to do so in the context of declining union recognition.…”
Section: Voluntarismsupporting
confidence: 71%
“…Although trade unions initially struggled to gain acceptance in Ireland they had gained a foothold in many key industries by the early 1900s. Hence for over a century IR in Ireland has been characterised by a strong collectivist orientation reflected in reasonably high levels of union density and a reliance on adversarial collective bargaining (Gunnigle and Morley, 1993;Gunnigle, 1995;Roche, 2001). While a detailed discussion of the IR system is beyond the scope of this paper, we draw on von Prondznski (1998) whose review of the main tenets of the Irish IR system concluded that these could be characterised thus:…”
Section: Industrial Relations In Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ireland, several studies have highlighted the marked increase in trade union avoidance, particularly among American MNCs establishing at greenfield facilities (cf. Gunnigle, 1995, Gunnigle et al, 1997Geary & Roche, 2001;Lavelle, 2008).…”
Section: Employer Approaches To Trade Union Avoidancementioning
confidence: 99%
“…This has involved granting legitimacy to "greenfield" sites, which permit firms to decide their preferred form of industrial relations (Gunnigle et al, 2001). Significantly for our study, research has indicated that it is particularly US MNEs that have used this latitude to implement US-style personnel policies (Gunnigle et al, 1997). …”
mentioning
confidence: 99%